Design and Analysis of a Metamaterial-Inspired Miniaturized Quadband Antenna - Si Li; Shitao Sun; Yunlong Mao (International Journal of Antennas and Propagation)
A metamaterial-inspired miniaturized quadband antenna is designed and discussed with a transmission line model to study the theory of miniaturization and multiband in this paper. A conventional printed monopole antenna is assumed as a primary antenna and then surrounded by an array of 4 × 2 interdigital LHMs. The proposed antenna has a compact size of 36mm×24mm×1mm, and operates at 2.40–2.55 GHz, 3.02–3.38 GHz, 5.04–5.52 GHz, and 7.08–7.38 GHz. Good gain and omnidirectional radiation patterns are observed in simulations and measurements. A simplified transmission line modal was established to study the reasons for miniaturization and multiband that were brought about by the LHM array. Related results verified the theoretical analysis and indicated that the proposed antenna is a good candidate for wireless communication applications.